The biopolymer bacterial nanocellulose as drug delivery system: Investigation of drug loading and release using the model protein albumin. Issue 2 (28th November 2012) - Müller, Astrid; Ni, Zhixu; Hessler, Nadine; Wesarg, Falko; Müller, Frank A.; Kralisch, Dana; Fischer, Dagmar
Abstract Although bacterial nanocellulose (BNC) has reached enormous interest for biomedical applications because of its outstanding material properties, investigations about its potential as drug delivery system are very rare. In the present study, for the first time, the applicability of BNC as drug delivery system for proteins using serum albumin as model drug was systematically investigated. Additionally, never‐dried BNC was compared with freeze‐dried BNC. For both types of BNC, a dependency of concentration, temperature, time, and preswelling for albumin loading and release could be demonstrated. These findings indicated an overlay of diffusion‐ and swelling‐controlled processes, which could be confirmed by Ritger–Peppas equation. Freeze‐dried samples showed a lower uptake capacity for albumin than native BNC, which was found to be related to changes of the fiber network during the freeze drying process as demonstrated by electron microscopy and protein staining experiments. The integrity and biological activity of proteins could be retained during the loading and release processes, which was demonstrated by gel electrophoresis and the use of luciferase as biologically active molecule. In conclusion, hydrophilicity, high biocompatibility, and controllable drug loading and release render BNC an innovative and attractive biopolymer for controlled drug delivery. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:579–592, 2013